If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -2) + -6x = 1 Reorder the terms: 5(-2 + 3x) + -6x = 1 (-2 * 5 + 3x * 5) + -6x = 1 (-10 + 15x) + -6x = 1 Combine like terms: 15x + -6x = 9x -10 + 9x = 1 Solving -10 + 9x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 9x = 1 + 10 Combine like terms: -10 + 10 = 0 0 + 9x = 1 + 10 9x = 1 + 10 Combine like terms: 1 + 10 = 11 9x = 11 Divide each side by '9'. x = 1.222222222 Simplifying x = 1.222222222
| 2x+2-25=3x+3 | | 5p-8=4p-1 | | -5y=0 | | -24+x=-3 | | -32=w-12 | | 7x+5*x=21+9x | | 9e^2+24e+16=0 | | -4y=-28 | | 30x^2+11x-30=0 | | 6y=-20 | | 8x-7+2x=6+5x+2 | | -75=3e | | 3x-7x^2=0 | | 70=2a | | n+11=-80 | | 3y+2=4y-(5-2y) | | 4(x-7)=3(x+6) | | 7+3=-29 | | 2x-(x-2)=30+x | | y=3x^5-3x^3-60x | | 9-(3a+5)=7-5a | | 5-(4-2x)+3(8x)=2 | | 3(x-1)=-3 | | 120-6x=30x+24 | | 12-9x=62-23x | | 8x=3x-5 | | -130-8x=7x+20 | | 2(x+3)=4(3+x) | | 5x+11=-109-7x | | 133-4x=5x+16 | | 2(x-3)=(3+x) | | -6(1-x)=6x-6 |